Genetic test results and one-year developmental outcomes of fetuses with congenital heart disease - Hu, Hui; Zhou, Bo; Shan, Qunda; Shen, Shuangshuang; Zhang, Xiangdong; Chen, Penglong; Liu, Jiao; Lan, Xiaofang (Frontiers in Pediatrics, 2025)
ObjectiveThis study evaluated the utility of single nucleotide polymorphism (SNP) microarray analysis in prenatal genetic assessment of fetuses diagnosed with congenital heart disease (CHD), retrospectively analyzing pregnancy outcomes and their association with physical and intellectual development within the first year of life.Patients and methodsIt included 105 fetuses diagnosed with CHD via prenatal echocardiography from January 2016 to June 2020, categorized into two groups: isolated cardiac structural abnormalities (76 cases) and additional extracardiac structural abnormalities (29 cases). All fetuses underwent chromosome karyotype and SNP array testing, with retrospective analysis of pregnancy outcomes, postnatal physical and intellectual development at one year of age.ResultsChromosomal abnormalities were identified in 15.2% (16/105) of the fetuses. A significantly higher incidence of chromosomal abnormalities was observed in the group with combined extra-cardiac structural abnormalities compared to the group with isolated cardiac abnormalities (P < 0.05). The detection rates of pathogenic Copy Number Variations (CNV), variants of uncertain significance (VOUS), and benign CNV showed no significant differences between the groups (P > 0.05). The detection rate of CNV was significantly lower in fetuses with isolated cardiac abnormalities (P < 0.05). The delivery rate was 61.0%, significantly higher in fetuses with only cardiac abnormalities. Of these, 38.5% of ventricular septal defects closed naturally within the first year. Only a small proportion of the children displayed developmental delays at one year of age.ConclusionSNP array analysis enhances the detection of genetic etiologies in CHD, assisting in the precise localization of chromosomal anomalies and candidate gene screening. It is effective for prenatal diagnosis in CHD fetuses. Fetuses with isolated cardiac structural abnormalities show lower rates of chromosomal anomalies and CNVs and generally have favorable one-year developmental outcomes, underlining the importance of SNP array analysis in managing CHD outcomes.